Survei Klasifikasi Minat Kerja Teori Anne Roe Dalam Pemilihan Karir Sesuai Kepribadian Siswa Pada Kelas IX SMP 1 Denpasar - Sri Muliya Hidayani; Luk Luk Yata Lalak Muslimin; Ni Wayan Suastini (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Work interest is a human tendency to focus attention on something they like and the needs that must be met to get satisfaction at work. The aim of this research is to determine the classification of work interests of class IX students at SMPN 1 Denpasar based on Anne Roe's classification of work areas according to the students' personalities. This type of research is a quantitative survey using a descriptive survey design involving class IX of SMPN 1 Denpasar. In this research, the sample was 22 students from each class IX of SMPN 1 Denpasar using a random sampling technique using an interest scale questionnaire. The method applied to collect data in this research uses questionnaires and observation. The results of this research show that: of the 22 respondents with 40 choice items, they chose SB 284 times, B 506 times, TB 168 times, and STB 2 times. The jobs that are most in demand by students are jobs in the service sector, 61 times chosen by students, and the jobs that are most unpopular with students are jobs in the field or outdoor sector with a score of 2 times. The results of the student categorization scores showed that 8 respondents (36%) were in the high category, 10 respondents were in the medium category (46%), and 4 respondents were in the low category (18%).